The Dynamics of Social Protection Gaps in Indonesia’s Transforming Labor Market: Gig Workers and Formal Employees - Lestari Agusalim; Puguh Prasetyoputra; Arissetyanto Nugroho; Dradjad Hari Wibowo (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2026)
Indonesia’s expanding gig economy has reshaped the labor market, offering flexibility while deepening social protection disparities. This study examines the gap in social protection coverage between formal employees and gig workers—online and local—within Indonesia’s employment landscape. Using microdata from August 2018, 2021, and 2023 National Labor Force Surveys (Sakernas), the analysis focuses on the service sector, where gig work is concentrated. A binary logistic regression with marginal effects was used to estimate the probability of workers’ participation in Indonesia’s social security programs. Findings revealed persistent, significant disparities: Online gig workers were 33% less likely and local gig workers 23% less likely to be covered than formal employees. These inequalities widened during and after the COVID-19 pandemic, especially in health and occupational accident insurance. Further analysis showed that disparities were more pronounced among male and urban workers. These results underscore structural vulnerabilities in Indonesia’s dual labor system and highlight the need for inclusive, adaptive social protection reforms. Recommendations include integrating gig workers into national social security schemes through shared contributions, strengthening digital and social protection literacy, and establishing a legal framework that recognizes platform-based employment as part of Indonesia’s labor market.